Motivation and background of participants and providers of self-harvest gardens in Germany. Issue 6 (8th December 2019) - Gauder, Martin; Hagel, Heinrich; Gollmann, Nadine; Stängle, Joachim; Doluschitz, Reiner; Claupein, Wilhelm
Abstract: Different forms of urban agriculture have gained increased interest and participation in Germany. One form of urban agriculture is self-harvest gardening where participants can lease a plot in a field with various vegetables. However, in Western Europe, little is known about self-harvest garden participants and providers or their motivation and social background. Therefore, in 2015 a survey was conducted with 173 participants and 34 providers from different regions and cities in Germany. The study aimed to compile a self-characterization of people engaged in this form of gardening on a national level. The outcome of the survey captures an emerging phenomenon. While many of the self-harvest gardens can be assigned as grassroot initiatives, participants generally characterized themselves as having a middle or high income, a sustainable lifestyle, high level of education and high nutritional awareness. Disproportionally often, females were engaged in self-harvest gardening. Providers were mainly farmers with a high affinity to organic agriculture. Often the farmers had synergistic effects with other activities like farm shops. Location of the garden area, good support by the providers, promotional marketing and social activities were identified as factors for successful self-harvest gardens. The main incentive for the participants seem to be their engagement in the production of local and healthy food, which can be taken into account by the providers when considering their future focus. On the other hand, problems with bad harvest, theft and vandalism were challenges for some self-harvest gardens. While, legal problems were not a major concern for the providers.